Highly orientated graphene/epoxy coating with exceptional anti-corrosion performance for harsh oxygen environments. (November 2020) - Wang, Xiao; Li, Yuan; Li, Cheng; Zhang, Xiguang; Lin, Dan; Xu, Fei; Zhu, Yanji; Wang, Huaiyuan; Gong, Jinlong; Wang, Tuo
Graphical abstract: Highlights: We designed a facile spin coating method and orientated graphene in epoxy matrix. The OG/EP coating has excellent anti-corrosion ability in harsh oxygen environments. The orientation of graphene in coating maximized the barrier effect of graphene. The orientation of graphene in coating prevented the formation of conductive network. Abstract: Herein, we designed a spin coating method and fabricated highly orientated graphene/epoxy (OG/EP) coating with long-term anti-corrosion performance. Surprisingly, the impedance at 0.01 Hz of OG/EP coating still remained at a relatively high value after 7 days of immersion in 3 MPa pure O2 and 3.5 wt% NaCl coupling environment, which was about 10 3 and 8 × 10 5 times higher than pure epoxy (Spin-EP and Spray-EP) and randomly arranged graphene/epoxy coatings', respectively. The protection mechanism of OG/EP coating is interpreted as the orientation of graphene, maximizing the barrier effect of graphene and avoiding the formation of graphene conductive network.